URGENSI E-SERVICE QUALITY UNTUK PENGUATAN KEPERCAYAAN DALAM KEPUTUSAN PEMBELIAN - Isalman; Ahmad Mubaraq; Conny; Ajeng Purwati Ningtyas (Jurnal Manajemen dan Kewirausahaan, 2025)
This study analyzes the role of e-service quality in building consumer trust in purchasing decisions on Shopee. Using a causal associative approach and explanatory research method, this study examines the relationship between variables using Structural Equation Modeling (SEM) through SmartPLS 3.0. The study population was the people of Kendari City who had made purchases on Shopee, with a sample size of 160 respondents selected by purposive sampling. The results of the study indicate that e-service quality has a positive effect on customer trust. This trust mediates the relationship between e-service quality and purchasing decisions. The theoretical implications of this study indicate the importance of digital service quality in strengthening the relationship between e-commerce platforms and consumers. Managerially, the results of this study suggest that e-commerce companies such as Shopee need to continue to improve service quality to build trust, maintain information transparency, and ensure a safe and comfortable shopping experience to attract and retain customers. Success in managing service quality drives repeat purchasing decisions, which contributes to business growth and sustainability.